DEVELOPMENT OF THE SKILLS OF STUDENTS TO AVOID TYPICAL ERRORS WHEN PERFORMING CUTTING AND CUTTING - Fakhriddin Uralovich Toshpulatov; Torayeva Feruza Murodaliyevna (Journals Park Publishing, 2022)
This article describes methodological recommendations on the mistakes made by students in cutting and cutting and their impact on learning the subject.
Keywords: knowledge; skill; competence